The effects of shell layer morphology and processing on the electrical and photovoltaic properties of silicon nanowire radial p+–n+ junctions. Issue 16 (28th April 2015) - Wang, Xin; Ke, Yue; Kendrick, Chito E.; Weng, Xiaojun; Shen, Haoting; Kuo, Mengwei; Mayer, Theresa S.; Redwing, Joan M.
<x xml:space="preserve">Abstract</x> Single wire p+–n+ radial junction nanowire solar cell devices were fabricated by low pressure chemical vapor deposition of n+ silicon shell layers on p+ silicon nanowires synthesized by vapor–liquid–solid growth.